A novel process route for the production of spherical LBM polymer powders with small size and good flowability - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Powder Technology, 2014)
Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, 'rapid prototyping' gradually is transferred to additive manufacturing opening new applications. At present basically only polyamide (PA) is available as an optimized powder material showing satisfying behavior during processing in laser beam melting (LBM). Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. We present a novel process chain for the production of spherical polymer micron-sized particles of good flowability that can be applied to a large variety of polymers: in a first step polymer particles are produced by a wet grinding method that are rounded in a second step using a heated downer reactor. To increase the flowability of the cohesive spherical polymer particles further nanoparticles are adhered to the particle surface in the third step. We demonstrate an increase of powder flowability by a factor of 5. The influence of particle habitus and nanoparticle functionalization on powder flowability is discussed in detail. © 2014 Elsevier B.V.
Keywords: Downer reactor; Dry particle coating; Flowability; Laser beam melting (LBM); Polymers; Wet grinding